Context Matters: Authoritarian Populism and Public Administration Practice, Teaching, and Research. Issue 7 (October 2022) - Box, Richard C.
The political context of public administration in the United States may change considerably in the near future, away from liberal democracy and toward an intensification of the authoritarian populism familiar from the Trump era. The people and practices of public administration experience the effects of the societal context in their daily work and the course of their careers, so that "context matters." This essay uses the description of the current context of the public sector at the federal, state, and local levels, and in academia, to examine the potential impacts of a contextual shift to authoritarian populism in the next several years. The examination includes daily practice, the teaching of controversial concepts in public universities, and conducting research on salient topics in public administration.